Lightweight and secure search scheme for medical data sharing - XIE Qingqing; SONG Liangqing; FENG Xia (Tongxin xuebao)
To balance the availability and security of medical data, a lightweight and secure search scheme was designed. The proposed search algorithm involved only two pairings and one multiplication operation, allowing for low consumption and security requirements when executing searches using smart contract. Additionally, the scheme employed key policy attribute-based encryption for fine-grained control over search operations, and utilized lightweight encryption algorithm and outsourced decryption mechanism to reduce computational overhead on user terminals. Finally, security analysis and experimental evaluations demonstrated the security and feasibility of the proposed scheme.